Antioxidant activity test on ambonese banana stem sap (Musa parasidiaca var. sapientum) - Hendrik Setia Budi; Indah Lisatiana Kriswandini; Aditya Dana Iswara (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Polymorphonuclear cells (PMN) release oxygen free radicals or reactive oxygen species (ROS) during inflammation. As a result, ROS level is higher than antioxidant level in our body during oxidative stress leading to prolong inflammation or continuous tissue damage. Indonesia, on the other hand, is a country with various herbal medicines. For instance, ambonese banana (Musa parasidiaca var. sapientum) is often used as herbal medicine. Ambonese banana, moreover, has flavonoid, polyphenol, tannin, and saponin as antioxidants to reduce free radicals by transferring their hydrogen atom. Medicine used to reduce the impact of free radicals is known as antioxidant. Antioxidant is proved to accelerate wound healing. Purpose: This research aims to analyze the effects of the antioxidant activity of Ambonese banana stem sap extract. Method: Antioxidant activities in this research were examined with 1,1-Diphenyl-2-picryl-hidrazyl (DPPH) method by reacting with stable radical compounds. Spectrophotometry with a wavelength of 517 nm was used to measure absorption results shown in purple. The absorption results then were calculated by IC50 reduction activity. Result: There were significant differences of Ambonese banana stem sap antioxidant activity (p<0.05) at the concentrations of 15%, 30%, and 60 %. All concentrations have greater absorbance scores than IC50 (>50%). Conclusion: Ambonese banana stem sap extract has antioxidant activities.